Dynamic region control for robot-assisted cell manipulation using optical tweezers - Li, X. (2013)
Current manipulation techniques of optical tweezers treat the position of the laser beam as the control input and an open-loop kinematic controller is designed to move the laser source. In this paper, a closed-loop robotic control method for optical tweezers is formulated and solved. While robotic manipulation has been a key technology driver in factory automation, robotic manipulation of cells or nanoparticles is less well understood. The proposed formulation shall bridge the gap between traditional robot manipulation techniques and optical manipulation techniques of cells. A dynamic region controller is proposed for cell manipulation using optical tweezers. The desired objective can be specified as a dynamic region rather than a position or trajectory, and the desired region can thus be scaled up and down to allow flexibility in the task specifications. Experimental results are presented to illustrate the performance of the proposed controller.